ROTACs leverage signaling-incompetent R-spondin for targeted protein degradation - Sun, Rui; Meng, Zibo; Lee, Hyeyoon; Offringa, Rienk; Niehrs, Christof (Cell chemical biology, 2023)
Proteolysis-targeting chimeras (PROTACs) are an emerging technology for therapeutic intervention, but options to target cell surface proteins and receptors remain limited. Here we introduce ROTACs, bispecific WNT- and BMP-signaling-disabled R-spondin (RSPO) chimeras, which leverage the specificity of these stem cell growth factors for ZNRF3/RNF43 E3 transmembrane ligases, to target degradation of transmembrane proteins. As a proof-of-concept, we targeted the immune checkpoint protein, programmed death ligand 1 (PD-L1), a prominent cancer therapeutic target, with a bispecific RSPO2 chimera, R2PD1. The R2PD1 chimeric protein binds to PD-L1 and at picomolar concentration induces its lysosomal degradation. In three melanoma cell lines, R2PD1 induced between 50 and 90% PD-L1 protein degradation. PD-L1 degradation was strictly dependent on ZNRF3/RNF43. Moreover, R2PD1 reactivates cytotoxic T cells and inhibits tumor cell proliferation more potently than Atezolizumab. We suggest that signaling-disabled ROTACs represent a paradigm to target cell surface proteins for degradation in a range of applications.
Online verfügbar: 14. Juni 2023, Artikelversion: 20. Juli 2023
Gesehen am 04.10.2023